The adequacy of retirement resources among the soon-to-retire, 1983 - 2001 - Edward N. Wolff (Levy Economics Institute of Bard College, 2006)
A central issue confronting soon-to-retire workers (those aged 4764) is whether they will have command over enough resources (both private and public) to maintain a decent standard of living in retirement. Typically, the adequacy of projected retirement income is judged in relation to some absolute standard (for example, the poverty threshold) and preretirement income (replacement rate). Using data from the Federal Reserve Board's Survey of Consumer Finances for 1983, 1989, and 2001, I find that expected retirement income grew robustly from 1989 to 2001 (by 38 percent in real terms) and the share with expected retirement income less than twice the poverty line fell by 5 percentage points. The percentage-point decline was even greater for minority households (11.6) and single females (5.7). The change in the share with replacement rates over 50 percent was 4.5 percentage points, though in this case much lower for minorities (0.9 percentage points) and single females (1.8 percentage points). However, percentage point changes for minorities and single females were much smaller, at 75 percent and a 100 percent replacement rates, respectively. Moreover, retirement wealth is very unevenly distributed. Whites and married couples had substantially larger wealth accumulations than their respective counterparts.
Keywords: J32; D31; H55; 330; pensions; Social Security; wealth; retirement adequacy